1
$\begingroup$

The EC action is given by:

$ S_{EC}= \int \epsilon_{abcd}e^a \wedge e^b \wedge R^{cd}$ where $R^{cd}=d\omega^{cd}+\omega^c_{ e}\wedge\omega^{ed}$

The Dirac action for the fermionic field in the EC formulation is given by:

$ S_D=i \kappa \int \epsilon_{abcd}e^a \wedge e^b \wedge e^c \wedge \bar \psi (\gamma^d \overleftrightarrow d + \{\gamma^d, \omega \} + \frac{im}{2}e^d)\psi $ where $\omega=\omega_{ab}[\gamma^a,\gamma^b]/8$.

The $\delta(S_{EC}+S_D)/\delta\omega$ eguation should give the torsion $T_a \equiv \nabla e_a = \frac{3\kappa}{4} i\epsilon_{abcd}e^b\wedge e^c \bar \psi \gamma^5 \gamma^d \psi $, but I have trouble deriving it. Where does $ \gamma^5$ come from?

$\endgroup$
  • 1
    $\begingroup$ Consider to spell out acronyms. $\endgroup$ – Qmechanic Apr 8 '17 at 19:18
1
$\begingroup$

So, I used the identity (which can be proved by expanding this anticommutator in terms of basis $\Gamma$)

$\{\gamma_\mu , \sigma_{\nu\rho} \}=-2\epsilon_{\alpha\mu\nu\rho}\gamma^5\gamma^{\alpha} $

$\frac{\delta S}{\delta \omega_{mn}}=-\epsilon_{abcd} de^a \wedge e^b + \epsilon_{abcd} e^a \wedge de^b+ \epsilon_{abcp} e^a \wedge e^b \wedge {\omega_d}^p - \epsilon_{abpd} e^a \wedge e^b \wedge {\omega_c}^p $

$\frac{\delta S_D}{\delta \omega_{mn}}=-\frac{\kappa}{4} \epsilon_{mnzd} \epsilon^{dabc}e_a \wedge e_b \wedge e_c \bar \psi (\gamma^5 \gamma^z) \psi$

Multiplying $\frac{\delta S+ S_D}{\delta \omega_{mn}}$with $\epsilon^{cdmn}$

$4(\nabla e^m)\wedge e^n-4(\nabla e^n)\wedge e^m+\frac{\kappa_1}{2}2 \begin{vmatrix} \delta^m_z & \delta^m_d \\ \delta^n_z & \delta^n_d \end{vmatrix} \epsilon ^{dabc}e_a \wedge e_b \wedge e_c \bar \psi (\gamma^3 \gamma^z)\psi$

$4 \nabla e^{[m} \wedge e^{n]}+\kappa _1 \epsilon ^{abc[n}e_a \wedge e_b \wedge e_c \bar \psi (\gamma^5 \gamma^{m]}) \psi =0$

$4 \nabla _\mu e^m \nu dx^ \mu \wedge dx^\nu e^n_\rho dx^\rho - 4\nabla _\mu e^n_\nu dx^ \mu \wedge dx^\nu e^m_\rho dx^\rho + \kappa_1 {\epsilon_{abc}}^m e^a_\mu dx^\mu \wedge e^b_\nu dx^\nu \wedge e^c_\rho dx^\rho \bar \psi (\gamma^5 \gamma^n)\psi - \kappa_1 {\epsilon_{abc}}^n e^a_\mu dx^\mu \wedge e^b_\nu dx^\nu \wedge e^c_\rho dx^\rho \bar \psi (\gamma^5 \gamma^m)\psi =0$

Multiplying with $dx^\sigma e^\alpha_m e^\beta_n$

$\epsilon^{\mu \nu \rho \sigma}(4 \nabla _\mu e^m_\nu e^\alpha _m \delta^\beta _\rho - 4\nabla_\mu e^n_\nu e^\beta _n \delta^\alpha_\rho + \kappa_1 {\epsilon_{abc}}^m e^a_\mu e^b_\nu e^c_\rho e^\alpha_m e^\beta_n \bar \psi (\gamma^5 \gamma^n)\psi - \kappa_1 {\epsilon_{abc}}^n e^a_\mu e^b_\nu e^c_\rho e^\beta_n e^\alpha_m \bar \psi (\gamma^5 \gamma^n)\psi) =0$

$\epsilon^{\mu \nu \rho \sigma}(4 \nabla _\mu e^m_\nu e^\alpha _m \delta^\beta _\rho - 4\nabla_\mu e^n_\nu e^\beta _n \delta^\alpha_\rho + \kappa_1 {\epsilon_{\mu \nu \rho}}^\alpha e^\beta_n \bar \psi (\gamma^5 \gamma^n)\psi - \kappa_1 {\epsilon_{\mu \nu \rho}}^\beta e^\alpha_m \bar \psi (\gamma^5 \gamma^n)\psi) =0$

$\epsilon^{\mu \nu \rho \sigma}(4 \nabla _\mu e^m_\nu e^\alpha _m \delta^\beta _\rho - 4\nabla_\mu e^n_\nu e^\beta _n \delta^\alpha_\rho) + \kappa_1(-6g^{\beta \sigma} e^\alpha_m \bar \psi (\gamma^5 \gamma^n)\psi +6g^{\beta \sigma}\bar \psi (\gamma^5 \gamma^n)\psi) =0$

Multiplying everthing with $\epsilon_{\gamma \delta \beta \sigma}$ and we get

$4(\nabla e^\alpha_{ \delta \gamma} -\nabla e^\nu _{\gamma \nu} \delta ^\alpha _\sigma + \nabla e^\nu _{\delta \nu} \delta ^\alpha _\gamma) - 6\kappa_1 g^{\alpha \tau}\epsilon_{\beta \tau \gamma \delta} \bar \psi (\gamma^5 \gamma^\beta)\psi + 6\kappa_1 g^{\beta \tau}\epsilon_{\beta \tau \gamma \delta} \bar \psi (\gamma^5 \gamma^\alpha)\psi =0$

Where $(\nabla e)^\alpha_{\mu \nu} = \nabla_\mu e^m_\nu e^\alpha_m$

For the contraction $\alpha = \delta$ we have $4(\nabla e^\alpha_{\alpha \gamma} -\nabla e^\nu _{\gamma \nu} 4 + \nabla e^\nu _{\gamma \nu}) = 0$

That means that $\nabla e^\nu_{\gamma \nu} =0$

Inserting this result into the previous equation, we get $4\nabla e^\alpha_{\delta \gamma} -6\kappa_1 g^{\alpha \tau}\epsilon_{\beta \tau \gamma \delta} \bar \psi (\gamma^5 \gamma^\beta)\psi =0 $

Using $\gamma^\beta=e^\beta_a \gamma_a$ , $\epsilon_{\beta \mu \gamma \delta} e_a^\beta =\epsilon_{abcd}e^b_\mu e^c_\gamma e^d_\delta$ and $\nabla e^\alpha_{\delta \gamma}=e^\alpha_b \nabla e^b_{\delta \gamma} $ we obtain wanted expression.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.